The effect of trust on loyalty with customer satisfaction as a mediation variable (Study on Gojek customers in Bandar Lampung) (Asian Journal of Economics and Business Management, 2023)
Service businesses such as online transportation are businesses based on the principle of trust. Gojek is the first online transportation service provider business in Indonesia. Now it has become the largest online transportation company in Indonesia. Online transportation is growing to the point where many new online transportation service operators increase competition in the online transportation market. Throughout 2022, many problems will occur between online transportation drivers and their customers, creating new anxiety among online transportation customers. It is feared that high competition and online transportation customer anxiety will reduce Gojek's customer loyalty. Customer satisfaction is an important element that can form customer loyalty. This study aims to examine the effect of trust on satisfaction and its effect on customer loyalty. Collecting research data using a questionnaire with a total sample of 150 respondents. Analysis of research data was carried out using SmartPLS version 3 software. The results showed that trust had a positive effect on satisfaction and loyalty, satisfaction had a positive effect on loyalty, and trust had a positive effect on loyalty, with satisfaction as a mediating variable.